2012
DOI: 10.1007/s00417-012-2165-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term visual outcomes of penetrating keratoplasty for Peters anomaly

Abstract: The results of delayed PKP in Peters anomaly were not inferior compared to the results of PKP performed at an earlier period in previous studies. If other congenital ophthalmic anomalies were present or graft rejection occurred within 1 month after PKP, the chance of graft failure was significantly increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
1
23
0
1
Order By: Relevance
“…Previous studies have shown that about 50% of patients with anterior segment dysgenesis develop glaucoma 38. The incidence of cases accompanied by glaucoma in our study was similar to that in previous reports 3 4 8. Assessing SD-OCT parameters may be useful for exploring the reason for high intraocular pressure in patients and for categorising Peters' anomaly, although independent studies with a larger sample size are warranted to verify our findings.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Previous studies have shown that about 50% of patients with anterior segment dysgenesis develop glaucoma 38. The incidence of cases accompanied by glaucoma in our study was similar to that in previous reports 3 4 8. Assessing SD-OCT parameters may be useful for exploring the reason for high intraocular pressure in patients and for categorising Peters' anomaly, although independent studies with a larger sample size are warranted to verify our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Corneal vascularisation was observed in 18 eyes (40.9%). A graft host disparity of 0.5–1.0 mm was used for the keratoplasty as described before 4. In the current study, the mean host cornea bed and the mean donor cornea button diameters were 6.3±0.2 and 7.1±0.2 mm, respectively.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Whether the IOL implantation will be performed depends on the age and ocular condition of patient [18, 19]. By measuring the size, location, and density of the opacity, penetrating keratoplasty may be considered, especially when the opacity obstructs the optical pathway [24]. Meanwhile, postoperative optical correction and occlusion therapy are necessary for better visual recovery.…”
Section: Discussionmentioning
confidence: 99%